Optimum Design to Minimum Cost of Sandwich Panels with Foam Core and Corrugated Faces - Cristina Vlădoiu; Liliana Bejan; N. Ţăranu (Bulletin of the Polytechnic Institute of Jassy: Constructions, Architechture Section, 2007)
The structural arrangement of sandwich panels with foam core and corrugated faces offers unique opportunities to mix and tailor materials and cross-section proportions to meet structural design criteria. For cost effective design, economic comparisons between combinations of different materials in sandwich structures must be made. Such comparisons should be based on sandwich proportions that vary for each combination of materials and that reflect the minimum combined cost of the core and facings. Simplified relations which can be used for economic analysis are proposed in the paper.